2021
DOI: 10.1016/j.jpra.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The management of deep sternal wound infection: Literature review and reconstructive algorithm

Abstract: Deep sternal wound infection (DSWI) is an important complication of open thoracic surgery, with a reported incidence of 0.5–6%. Given its association with increased morbidity, mortality, inpatient duration, financial burden, and re-operation rates, an aggressive approach to treatment is mandated. Flap reconstruction has become the standard of care, with studies demonstrating improved outcomes with reduced mortality and resource usage in patients undergoing early versus delayed flap reconstruction. Despite this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 61 publications
1
43
1
3
Order By: Relevance
“…The current series of 105 patients examined in this study support our previous findings that this treatment yields excellent functional outcomes in highly morbid patient population 7 . In contrast to the mortality rate of 14% to 47% in the literature, we had a 10% 30-day mortality rate noted 12,14,15,27 . Critically, 80% of the patients in this cohort had at least 1 comorbidity, and 90% of patients who passed away had more than 1 concurrent disease.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The current series of 105 patients examined in this study support our previous findings that this treatment yields excellent functional outcomes in highly morbid patient population 7 . In contrast to the mortality rate of 14% to 47% in the literature, we had a 10% 30-day mortality rate noted 12,14,15,27 . Critically, 80% of the patients in this cohort had at least 1 comorbidity, and 90% of patients who passed away had more than 1 concurrent disease.…”
Section: Discussioncontrasting
confidence: 77%
“…Critically, 80% of the patients in this cohort had at least 1 comorbidity, and 90% of patients who passed away had more than 1 concurrent disease. We treated an aged population with a variety of medical risk factors yet managed to decrease our mortality rate from 16% to 10% in the last 16 years 7,14,28 . Prior groups have shown that poor nutrition, IMA use, renal failure, and longer time interval between operation and reconstruction are associated with increased mortality and morbidity in chest wall flap-based reconstruction 11–13,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, flap reconstruction is regarded as the gold standard in DSWI where there is inadequate sternum following debridement or uncertainty whether the infectious process has been controlled [22]. There has been a variety of flap choices for reconstructing sternal wounds, such as the pectoralis major flap, rectus abdominis flap and omental flap.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Weinand et al preserve this flap for wounds exceeding 12 cm in width, recommending unilateral or bilateral pectoralis flap reconstruction for defects narrower as 6 and 12 cm respectively [ 8 ]. Hever et al, recommends superior sternum reconstruction with a turnover flap based on perforators of the internal mammary artery or bilateral pectoral advancement flap or the latissimus dorsi flap, whereas he recommends the rectus abdominis flap for inferior sternum reconstruction [ 14 ]. Greig et al propose the use of either pectoralis major or combined pectoralis major and rectus abdominis flaps [ 13 ].…”
Section: Discussionmentioning
confidence: 99%